(untitled) (Journal of NELTA, 2022)
This study aimed to explore the English language (EL) teachers’ induction phase in Bangladesh, focusing on the usual practices, challenges they face, and their expectations. Teachers’ induction phase is immensely signiﬁcant as they make a transition to the teaching profession. Following the qualitative phenomenological approach, qualitative data were collected from six (6) EL teachers working at the primary, secondary, and higher secondary levels across Bangladesh through interviews. The collected data were analysed using the thematic analysis framework as advocated by Braun and Clarke (2006). The key ﬁndings included a three-segment teacher recruitment mechanism, absence of pre-service teacher preparation and adequate initial training, varied initial experiences of teachers, no mentoring and observation, limited collaboration, and inadequate opportunity for professional development. Moreover, the ﬁndings also revealed that many such teachers are confused regarding their career because of discrepancies between pre-service perceptions and in-service actualities, lack of required support and resources for novice teachers, the signiﬁcance of teachers’ proactive role in induction, and their confusion about career planing.